Fluxos rizomáticos do Conselho Municipal de Saúde em Afonso Cláudio-ES : cartografia de uma participação social - Saleme, Roberta Bissoli (2012)
The institutionalization of the Health Councils is important for the democratization of municipal health policy, since it allows the expansion socio-political actors’ participation in the colletive decision-making process. But merely creating the device "Council" does not guarantee the effective representativeness associated to it. It is known that social control is currently a challenge in public administration. Municipal Councils, the object of this study, constitute themselves as deliberative potencies to assist managers overcome this challenge. Given this context, it was defined as general purpose to describe and to analyze the process of social participation in health in the city of Afonso Cláudio-ES through the Municipal Health Council of Afonso Cláudio (CMSAFC) and its advisers. This research is methodologically characterized as a documental analysis study with cartographic nature. We analyzed the CMSAFC’s minutes and resolutions concerning the period between March 31, 2010 and March 31, 2011. The general objective’s achievement took place through the specific aims outlined to get to know the devices established about social participation in the CMSAFC as well as to discuss if the group's advisers movement occurs merely in order to legitimize what is established or to create new ways of thinking and doing the popular participation in health in the city. This study brings social participation in Brazil to the discussion, with regards to the issues of democracy and management, and also discusses the characterization of health councils in the country, quoting their legal duties and the institutionalization process at the national level to weave the cartography of the CMSAFC’s specific case. The study showed that social participation through the CMSAFC is characterized by a web of relationships, whose rhizomatic flows occur in a continuous and intense way, producing social reality. It was demonstrated the assemblage of connections and flows, through the ways of insertion and participation of advisers, whose actions - powers - produce each day new ways of thinking and doing social control. The production of participation in the meetings allowed the creation of different intensities flows, affections which interpenetrated and intercrossed themselves in various directions in a rhizomatic way, promoting new ways to operationalize social participation.